PENGARUH PEMBERIAN DOLOMIT DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) DI LAHAN GAMBUT - Bayu Ariska Andriani; Syafrinal Syafrinal; Isna Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the interaction of dolomite and chicken manure to get the best dosage combination on the growth and yield of onion at peatlands. This research was conducted on peat land located in Pematang Reba, Rengat Barat, Indragiri Hulu Regency. This study used Factorial Randomized Block Design (RAK) with two factors. The first factor was doses of dolomite fertilizer (D) (2, 4 and 6 tons.ha-1) and the second factor was the doses of chicken manure (K) (5, 10 and 15 kg.ha-1). The parameters observed were plant height, number of leaves, number of tubers, tuber bulbs, fresh weight tuber.plot-1, and reasonable save tuber weight.plot-1. Based on the result of the research, of dolomite and chicken manure give an effect on the parameters of plant height, fresh weight tuber.plot-1, and reasonable save tuber weight.plot-1. However, it was not give an effect on the number of leaf parameters, the number of tubers and the tubers. Based on the result of the research, the combination of dolomite treatment of 400 g.m-2 and chicken manure 1000 g.m-2 resulted in the fresh weight tuber.plot-1, and reasonable save tuber weight.plot-1 higher than other treatment.Keywords: onion, dolomite and chicken manure